#### Question

Find the value of ‘m’, if mx^{3} + 2x^{2} – 3 and x^{2} – mx + 4 leave the same remainder when each is divided by x – 2

#### Solution

Let f(x) = mx^{3} + 2x^{2} – 3

g(x) = x^{2} – mx + 4

It is given that f(x) and g(x) leave the same remainder when divided by (x – 2). Therefore, we have:

f (2) = g (2)

m(2)^{3} + 2(2)^{2} – 3 = (2)^{2} – m(2) + 4

8m + 8 – 3 = 4 – 2m + 4

10m = 3

m = `3/10 `

Is there an error in this question or solution?

Solution Find the Value of ‘M’, If Mx3 + 2x2 – 3 and X2 – Mx + 4 Leave the Same Remainder When Each is Divided by X – 2 Concept: Remainder Theorem.